The moral and a political portrait of great figures of histroy in the Library of History of Diodorus Siculus (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
The article deals with the importance given to the war by historians of antiquity as an important part of his narrative construction and description of the deeds of great men. It seeks to deepen the importance of the war for the construction of men considered wise and important to the historian Diodorus of Sicily as the story is, for him, a court, where everyone will be judged for good or for evil.